Comparisons of Elasto-Fiber and Fiber & Bernoulli-Euler reinforced concrete beam-column elements - Karaton, Muhammet (Techno-Press, 2014)
In this study, two beam-column elements based on the Elasto-Fiber element theory for reinforced concrete (RC) element have been developed and compared with each other. The first element is based on Elasto Fiber Approach (EFA) was initially developed for steel structures and this theory was applied for RC element in there and the second element is called as Fiber & Bernoulli-Euler element approach (FBEA). In this element, Cubic Hermitian polynomials are used for obtaining stiffness matrix. The beams or columns element in both approaches are divided into a sub-element called the segment for obtaining element stiffness matrix. The internal freedoms of this segment are dynamically condensed to the external freedoms at the ends of the element by using a dynamic substructure technique. Thus, nonlinear dynamic analysis of high RC building can be obtained within short times. In addition to, external loads of the segment are assumed to be distributed along to element. Therefore, damages can be taken account of along to element and redistributions of the loading for solutions. Bossak-alpha integration with predicted-corrected method is used for the nonlinear seismic analysis of RC frames. For numerical application, seismic damage analyses for a 4-story frame and an 8-story RC frame with soft-story are obtained to comparisons of RC element according to both approaches. Damages evaluation and propagation in the frame elements are studied and response quantities from obtained both approaches are investigated in the detail.
Keywords: Elasto-Fiber element; Fiber & Bernoulli-Euler element; seismic damage analysis; dynamic substructure technique; Bossak-alpha method and predicted-corrected method